First-principles study of stability and electronic properties of single-element 2D materials - D. C. Hvazdouski (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
We have estimated stability of single-element 2D materials (C2, N2, Si2, P2, Ge2, As2, Sn2, Sb2, Pb2, and Bi2) by ab initio calculations. The calculations of structural and mechanical properties of 2D materials were performed using the VASP software package. The results of calculations of stiffness tensors, Young's modulus, and Poisson's ratios show that all studied single-element 2D materials are mechanically stable. Dynamic stability was investigated by calculating the phonon dispersion of the materials using the finite displacement method. Only Pb2 has imaginary modes in the phonon dispersion curves and therefore it has dynamic unstable structure at low temperatures. The analysis of the band structures indicates the presence of insulators (N2), semiconductors (P2, As2, Bi2, Sb2), semimetals, and metals among the studied group of single-element 2D materials.